A series of high-temperature molecular ferroelectric crystals: chlorine doped diisopropylammonium bromide. Issue 10 (16th February 2016) - Gao, Kaige; Liu, Chuang; Cui, Zepeng; Xu, Cong; Zhu, Jiansheng; Gao, Linsong; Cai, Hong-Ling; Wu, X. S.
Abstract : A series of chlorine doped diisopropylammonium bromide (DIPAB-C) single crystals were grown successfully. Abstract : A series of chlorine doped diisopropylammonium bromide (DIPAB-C) single crystals were grown successfully. The DIPAB-C crystals have two phase transitions (from P 21 21 21 to P 21 at T 1, and from P 21 to P 21 / m at T 2 ) in the warming process but only one ( P 21 / m to P 21 ) in the cooling process. The ferroelectric-to-paraelectric transition temperature can be modulated from 423 K to 429 K by chlorine concentration. The spontaneous polarization decreased from 23 μC cm −2 for undoped DIPAB crystals to 13 μC cm −2 for a chlorine concentration of x = 0.08, then it had a stable value of 14 μC cm −2 for x > 0.1. This indicates that the ferroelectric properties, including spontaneous polarization, the phase transition temperatures, the lattice parameters, etc., can be modulated by doping with congeners.